Synthesis and Therapeutic Potential of Oxadiazole Scaffolds: A Comprehensive Review of Recent Advancements - Bhaumik, Asish; Das, Lipika; Vikram, Kumar; Paul, Sahishnu; Lahon, Disha; Sarmah, Amitrajit; Kashyap, Anushka; Bhowmik, Prasanta (Journal of Neonatal Surgery, 2025)
Oxadiazole is a versatile heterocyclic compound with a five-membered ring containing both oxygen and nitrogen, which has sparked significant interest in medicinal chemistry. The synthesis of oxadiazole derivatives typically involves the condensation of hydrazides with carbonyl compounds or other reactive intermediates under acidic or basic conditions. Common methods to form these compounds include cyclization reactions, Minnich-type reactions, and the use of catalysts such as phosphorous oxychloride and carbon disulfide (CS2). Biologically, oxadiazole derivatives exhibit a broad range of pharmacological activities, including antimicrobial, anti-inflammatory, anticancer, and antidiabetic effects. They show strong antimicrobial activity against both Gram-positive and Gram-negative bacteria, as well as fungi, often exceeding the potency of standard antibiotics. In cancer research, oxadiazole derivatives inhibit tumour progression by targeting enzymes like telomerase and disrupting cell division mechanisms. Additionally, many of these compounds display significant anti-inflammatory properties, making them potential candidates for treating chronic inflammatory diseases like arthritis.